Effectiveness of Financial Support for Recovery from Covid-19 in Road Sector - Тзоневска, Дина (Научни трудове, 2023)
All the restrictions and closures of borders and the impact of the coronavirus pandemic have put us in front of the greatest economic challenge we have faced in decades. The decline in car traffic means less revenue, while truck traffic has recovered from the crisis faster. The Covid-19 pandemic is also having a significant impact on our transport systems. European supply chains are closely linked. These connections are maintained through a wide network of freight transport services. Interruptions in these flows of goods lead to serious economic damage. The problem that will affect road hauliers the most is liquidity. The economic outlook and huge projected losses across the transport sector would lead to bankruptcy in the coming months and years. Comparing the importance to realization, it is necessary for road hauliers to focus governments on providing targeted cash benefits and to facilitate flexibility in terms of insurance premium payment conditions. The European Recovery Plan is the EU’s main instrument for supporting investment and reform in the Member States and helping companies and workers to overcome the Covid-19 crisis.
Keywords: Ефективност на финансовата подкрепа; Възстановяването от COVID-19; Пътен сектор; Финансова подкрепа; Европейски план за възстановяване